1989
DOI: 10.1111/j.1365-2125.1989.tb05384.x
|View full text |Cite
|
Sign up to set email alerts
|

Captopril: a free radical scavenger.

Abstract: The use of captopril in heart failure and hypertension is becoming increasingly accepted. Captopril has a sulphydryl group in its molecular structure. We wondered if this might confer free radical scavenging activity on the drug and have investigated this in an in vitro system. Results show that captopril is a free radical scavenger and we suggest that this action might be relevant in its use in heart failure and other vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 10 publications
3
46
0
Order By: Relevance
“…Other studies have also reported the ability of captopril to scavenge -OH radicals, 31 as well as exhibit general free radical scavenging activity. 32 In our present study, we also found that in contrast to captopril, the non-SH-containing ACE inhibitor enalaprilat exhibited only slight (nonsignificant) protection, indicating the ACE inhibition may not be the only mechanism of protection by captopril.…”
Section: Discussionsupporting
confidence: 55%
“…Other studies have also reported the ability of captopril to scavenge -OH radicals, 31 as well as exhibit general free radical scavenging activity. 32 In our present study, we also found that in contrast to captopril, the non-SH-containing ACE inhibitor enalaprilat exhibited only slight (nonsignificant) protection, indicating the ACE inhibition may not be the only mechanism of protection by captopril.…”
Section: Discussionsupporting
confidence: 55%
“…ACE inhibitors are applicable in the prevention of hypertension as mentioned by Mark and Davis (2000), which proposed for the treatment of cancer (Lever et al 1999). Consequently, the urgency for natural food-born ACE inhibitors compared to the adverse effects (hypotension, cough, hyperkalemia, headache, dizziness, fatigue, nausea, and renal impairment) of clinically used synthetic ACE inhibitors such as Captopril, have guided to this research (Chopra et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some reported a high superoxide scavenging activity, whereas others found that captopril removed superoxide inefficiently. Chopra et al [5], using the technique described by Misra and Fridovich [15], demonstrated that captopril specifically scavenges O 2 -. On the other hand, Winterbourn & Metodiewa [16] as well as Kukreja et al [17], using a number of superoxide-generating systems such as xanthine-xanthine oxidase, phorbol myristate acetate-activated neutrophils, auto-oxidizing dihydroxyfumarate, and auto-oxidation of epinephrine to adrenochrome, asserted that captopril does not scavenge superoxide anion.…”
Section: Discussionmentioning
confidence: 99%
“…Much of it is carried as adsorbed captopril or as disulphydes with endogenous sulphydril-containing compounds such as glutathione and plasma proteins [4]. In this way, it can serve as the depot of the drug and could function as recyclable antioxidant agent [5].…”
Section: Introductionmentioning
confidence: 99%